A Global Analysis of Y-STR INRA189 Polymorphism in Chinese Domestic Yak Breeds/Populations - Ma, Z.; Xia, X.; Chen, S.; Bai, M.; Lei, C.; Han Jianlin (MDPI, 2020)
The objective of this study was to probe into the polymorphism of Y-STR INRA189 and identify the geographical distribution pattern of its alleles in the Chinese domestic yak gene pool. We examined the variation at INRA189 locus in 682 male yaks representing 15 breeds/populations in China. The results showed that six alleles, including five reported previously (149, 155, 157, 159, and 161 bp) and a new one identified in this study (139 bp), were detected at INRA189 locus based on genotyping analysis. The frequencies of six alleles varied among the 15 yak breeds/populations with a clear phylogeographical pattern, which revealed the paternal genetic difference among Chinese yak breeds/populations. The average polymorphism information content (PIC) among the 15 yak breeds/populations was 0.32, indicating INRA189 to be an intermediate polymorphic Y-STR marker (0.25 < PIC < 0.5) in yak. Sequence alignment revealed that the variations among six alleles at INRA189 were defined by a TG dinucleotide repeat motif, which repeated for 12, 17, 20, 21, 22, and 23 times, corresponding to the alleles of 139, 149, 155, 157, 159, and 161 bp, respectively. Therefore, we believe that the polymorphic yak Y-STR INRA189 can be used to characterize male-mediated genetic events, including paternal genetic origin, diversity, and evolution.